Characteristics of plasma electrolytic oxide coatings on Mg-Al-Zn alloy prepared by powder metallurgy - Chang, Si Young; Lee, Du Hyung; Kim, Bo Sik; Kim, Taek Soo; Song, Yo-Seung; Kim, Sung Ho; Lee, Chan Bok (Metals and materials international, 2009)
Mg-6 wt.%Al-1 wt.%Zn alloy powders were produced by gas atomization, and subsequently compacted and sintered under various conditions of temperature, time, and pressure. The bulk Mg-6 wt.%Al-1 wt.%Zn alloy was coated by the plasma electrolytic oxidation (PEO) method. The optimum condition of compaction and sintering for PEO coatings was established based on the investigation of microstructure, microhardness, and corrosion properties of coatings which were compared to those of cast Mg-6 wt.%Al alloy. The coatings on Mg-6 wt.%Al and Mg-6 wt.%Al-1 wt.%Zn alloys consisted of MgO, MgAl 2 O 4 , and Mg 2 SiO 4 . The Mg-6 wt.%Al-1 wt.%Zn alloy compacted at room temperature for 10 min and sintered at 893 K for 3 h showed the most porous and nonuniform coating layer because the coatings had grown through grain boundaries that resulted from poor bonding between powder particles in the substrate. However, the coated Mg-6 wt.%Al-1 wt.%Zn alloy hot-compacted at 593 K for 10 min had the thickest coating layer and the highest microhardness. In addition, it demonstrated the best corrosion resistance as verified by polarization curves in 3.5% NaCl solution.